THE ADDED VALUE OF SHREDDED LELE AND PATIN CATFISH - Ristina Siti Sundari; Andri Kusmayadi; Dona Setya Umbara (Agros Journal of Agriculture Science, 2017)
Fish is not only perishable product but also has segmented market. Consumption market such wants the fresh fish and certainty size. The problem is when the size of fish is too big for consumption, so that product is not wanted by consumer anymore. This research aimed at knowing the added value of shredded Lele and Patin catfish agribusiness and increasing prosperity of humanitarian society throughout processing the shredded catfishes. The data of this research was analyzed by Added Value Analysis of Hayami. The result showed that the shredded product of Lele catfish gave the added value IDR 14.295,00 per kilograms with the added value ratio was 25,53 percent and Conversion value was 0,35. Whereas, the shredded product of Patin catfish gave the added value IDR 18.295,00 per kilogram with the added value ratio was 29,04 percent and Conversion value was 0,35. The agribusiness toward processing and marketing of shredded Lele and Patin catfish was innovative agribusiness that could develop business opportunity so that it could move on the economical wheel and increasing humanitarian society prosperity actively. The market demand was still very wide either in town or out of town. The partnership among various not only government but also non government associations would be a good matter toward this agribusiness is running well.